Comparison of Psychometric Characteristics for Five Versions of the Interpersonal Needs Questionnaire in Teenagers Sample - Quan, Jiaxin; Yu, Xiaofang; Cai, Yan; Tu, Dongbo (Frontiers in Psychology, 2021)
Interpersonal Needs Questionnaire (INQ) is a self-report measure of perceived burdensomeness (PB) and thwarted belongingness (TB) with five versions in recent studies. There are five versions of INQ. But results from studies using different versions are quite different. Current suicide behavior among teenagers has attracted much attention. But which version is more suitable for teenage samples is still uncertain. It is important to compare the potential differences in different versions of INQ to identify the most psychometrically available version to predict teenagers’ acquired capability for suicide and provide them with timely help to reduce teenagers’ suicide rates. This study compared the construct validity, internal consistency, validity and average test information of each version in the sample of teenagers. Results showed the 10-item version provided the most average test information in both TB subscale and PB subscale and the INQ-10 is more suitable for teenage samples.